Function Follows Form: Using the Aesthetic Association Principle to Enhance Haptic Interface Design - Breitschaft, Stefan Josef; Carbon, Claus-Christian (Frontiers in Psychology, 2021)
Novel tangible user interface technologies facilitate current trends towards seamless user interfaces. They enable the design of yet unseen interfaces and thus the creation of a new kind of haptic language. In order to use the benefits of a touch-and-feel design for positive user experience, carefully designed haptic feedback plays an important role by providing aesthetically pleasing and sustainable product features. Haptic feedback may exceed a mere acquiring of buttons and input-confirmation but enable orientation and even identification of functionality governed by the haptic impression. We employed the Aesthetic Association Principle as a deeply grounded psychological mechanism that assists effective linkage between haptic form factors and associated functional attributes. In order to illustrate this powerful principle, we analyzed the specific associations between certain main haptic surface qualities and associated functional aspects. In a series of three subsequent studies (Pre-Study 1: Perception, Pre-Study 2: Similarity and Main Study: Association), we explored paradigmatic associations of that kind to develop guidelines which forms are distinct to be used in interfaces. We show how forms are implicitly categorized into functional qualities (on/off, more-less, selection) using a multidimensional scaling procedure and explore explicit form-functionality associations using a think-aloud-method in the context of an automotive interface. For a series of forms, we revealed clear associative relations to specific functions. We will discuss the general value and opportunities of an association-based approach to user experience in order to create intuitive user interfaces. We will also develop ideas for specific areas of applications.